2023
DOI: 10.3390/bioengineering10050621
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow-Derived Mesenchymal Stem Cell Applications in Neurodegenerative Disease Treatment and Integrated Omics Analysis for Successful Stem Cell Therapy

Abstract: Neurodegenerative diseases (NDDs), which are chronic and progressive diseases, are a growing health concern. Among the therapeutic methods, stem-cell-based therapy is an attractive approach to NDD treatment owing to stem cells’ characteristics such as their angiogenic ability, anti-inflammatory, paracrine, and anti-apoptotic effects, and homing ability to the damaged brain region. Human bone-marrow-derived mesenchymal stem cells (hBM-MSCs) are attractive NDD therapeutic agents owing to their widespread availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 134 publications
(175 reference statements)
0
3
0
Order By: Relevance
“…Stem cell transplantation is emerging as a promising treatment for ischemic diseases, as research has confirmed the beneficial therapeutic effects of stem cells in both clinical and experimental models [ 34 ]. Among various stem cells, adult mesenchymal stem cells (MSCs), particularly bone marrow-derived stem cells (BMSCs), show potential due to their high self-renewal, differentiation capacity, and low immunogenicity for the treatment of ischemic diseases [ 35 , 36 ]. Limitations include restricted available BMSCs from patients and an age-related decline in their proliferation and differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell transplantation is emerging as a promising treatment for ischemic diseases, as research has confirmed the beneficial therapeutic effects of stem cells in both clinical and experimental models [ 34 ]. Among various stem cells, adult mesenchymal stem cells (MSCs), particularly bone marrow-derived stem cells (BMSCs), show potential due to their high self-renewal, differentiation capacity, and low immunogenicity for the treatment of ischemic diseases [ 35 , 36 ]. Limitations include restricted available BMSCs from patients and an age-related decline in their proliferation and differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…Primary approaches under exploration for utilizing these vesicles in treatments encompass strategies like using vesicle-releasing cells on-site, injecting purified or modified vesicles, and implanting modified cells that produce tailored vesicles within the body [102][103][104]. Examples include investigating mesenchymal stem cell-derived vesicles for treating conditions like cerebellar ataxia, bone repair, and eye issues [105,106]. Additionally, there has been extensive research into loading isolated vesicles with specific substances or modifying their surfaces for enhanced delivery, targeting ailments such as stroke and pancreatic cancer [99,100,107].…”
Section: Applications Of Extracellular Vesiclesmentioning
confidence: 99%
“…Parkinson's disease (PD) and multiple sclerosis are chronic, progressive neurodegenerative pathologies that are quite common in Ukraine and tend to increase [1,2]. Today, the transplantation of multipotent mesenchymal stromal cells (MMSCs) from various sources, in particular bone marrow, is an important direction of cell therapy for the above-mentioned pathologies [3][4][5]. This is related to the biological properties of MMSCs, namely the ability to multilineage differentiation, the synthesis of neurotrophic factors, anti-inflammatory, antioxidant and immunomodulatory effects.…”
Section: Abstract: Parkinson's Disease/parkinsonism; Multiple Scleros...mentioning
confidence: 99%
“…Bone marrow cells were obtained from mice of each group on the 18 th day of the experiment and incubated for 12 days to further evaluate the colony-forming ability of stromal progenitor cells [21]. It is MMSCs that are successfully used in cell therapy of neurodegenerative pathology [3]. Bone marrow cells (1×10 6 ) of FVB/N and 129/Sv mice, which were injected with MPTP, were incubated with melatonin (Sigma, USA) at a dose of 0.1 μg/0.1 mL or without it.…”
Section: Animalsmentioning
confidence: 99%